Collaboration in Developing Wotgalih Village’s Local Potential through the Integration of Water Hyacinth and Batik Based on Social Entrepreneurship to Achieve a Sustainable Creative Economy - Ilmiyah, Fadhilatul; Bahrian, Nanda Eka; Afkarinah, Isna Duriyah; Ramadhan, Bima Wahyu Gilang; Meilan, Ria (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2026)
The Student Organization Capacity Building Program (PPK Ormawa) in Wotgalih Village, Yosowilangun District, Lumajang Regency, was implemented to empower the community by leveraging local potential. Wotgalih Village has abundant natural resources, including water hyacinths, and a strong batik-making tradition, both of which are underutilized. Through training, mentoring, and integrated production, the program transforms these potentials into creative, valuable products: “Gondo Laut” Batik packaged with woven water hyacinth crafts. Methods include observation, interviews, pre- and post-test questionnaires, and participatory evaluations to assess skill improvement and program effectiveness. Results show a significant rise in the community’s ability to process local materials into marketable goods, the formation of the “Guyub Ranu Batik” business group, and increased entrepreneurship among women and youth. The program also fosters collaboration among universities, the village government, and local communities to build a creative economy rooted in local wisdom. This activity improves economic welfare, strengthens cultural identity, and establishes an innovative, sustainable model for village development.